Mr. Lemoncello's Library Olympics - Grabenstein, Chris (Yearling, 2017)
Mr. Luigi Lemoncello invites teams from across the United States to his first-ever Library Olympiad. Kyle and his teammates arrive for the games but notice books missing from the library. Someone is censoring what the kids are reading, and Mr. Lemoncello needs their help to find out who is stealing his books.